PREGNANCY OUTCOMES OF CONSANGUINITY AMONG ANTENATAL PATIENTS ATTENDING COMBINED MILITARY HOSPITAL QUETTA, PAKISTAN - Abrar, Saidul; Safdar, Wajiha; Hanif, Muhammad; Shujaat, Nusrat (Journal of Ayub Medical College Abbottabad, 2018)
Background: All definitions of consanguinity encompass the basic concept of close blood relation. Highest rates of consanguineous unions are observed for North and Sub Saharan Africa, Middle East, and west, central and south Asia, where 20-50% marriages are consanguineous. In Pakistan, we can hardly find any rigorous research on the pregnancy outcomes of consanguinity except those conducted by Allan Bittles. This study was conducted with the objective to measure statistically if there existed any association of consanguinity with pregnancy outcomes in the form of stillbirths, abortion and Rh-incompatibility. Methods: This cross sectional analytical study was conducted at the Obstetrics department of Combined Military Hospital Quetta, Pakistan from 1st November 2017 to 28th February 2018. All pregnant women visiting Out Patient Department were included. Women unwilling to participate or needing emergency intervention were excluded. Sample size, i.e., 384 was calculated using online OpenEpi calculator and simple random sampling technique was applied. A structured interviewer administered questionnaire was used to extract retrospective information. Descriptive statistics,95% Confidence Intervals, Chi-Square test and Contingency Coefficient were calculated using SPSS Version 20. Results were regarded significant at p<0.05. Results: Out of 384 study participants, 188 (48.9% with 95% CI:43.9-53.9%) were married to first cousins. Mean±SD age of the study participants was 27.5±4.8 years. Difference between stillbirth, and abortion among consanguineous unions and non-consanguineous unions was significant while that of Rh-incompatibility was non-significant. Conclusion: Large population based studies are needed before declaring consanguinity as a health problem in our setting. Keywords: Consanguinity; Stillbirth; Abortion